Legal Alignments for Post-Divorce Muallaf Women in the Multicultural Society of Manado City - Sarib, Suprijati; Alimashariyanto, M.; shairgojri, Aadil Ahmad (Madania: Jurnal Kajian Keislaman, 2022)
This study analyzed the legal alignment for post-divorce muallaf women through the decision of the Religious Courts and the implementation in Manado City. This investigation was necessary due to the high rates of male and female muallaf marriages in this city. The rights of muallaf women have been neglected after divorce, specifically those relating to livelihoods and children. However, legal alignment is a reality, providing there is reinforcement from the court as stipulated in the 1945 Constitution article 27 paragraph 1. A Qualitative method with a normative-sociological approach was used in analyzing the data. The primary data sources were informants, comprising people who changed religion because of marriage, as well as government and clergy officials. In addition, library materials were used after seriously studying the literature such as journal articles, books, and other supporting documents that relevant to this research. The findings showed that legal protection for the rights of post-divorce muallaf women was not solely the judge’s decision on paper but the responsibility of men that was to be fulfilled after the divorce. Although these rights were not adequately realized, it is concluded the tendency for muallaf women to obtain their rights with good cooperation from all litigants, including the law enforcers. This study suggested that the form of legal alignment for women based on the law is not only on paper but also an evaluation is needed from law enforcers. Studi ini menganalisis keberpihakan hukum bagi perempuan muallaf pasca bercerai lewat putusan Pengadilan Agama dan sejauhmana pengimplementasiannya bagi perempuan muallaf pasca bercerai di Kota Manado. Penyelidikan ini diperlukan karena tingginya angka perkawinan muallaf laki-laki dan perempuan di kota ini. Hak-hak perempuan muallaf, khususnya yang berkaitan dengan nafkah, anak, dan setelah perceraian, terabaikan. Padahal keberpihakan hukum menjadi kenyataan, asalkan ada penguatan dari pengadilan sebagaimana diatur dalam UUD 1945 pasal 27 ayat 1. Metode kualitatif dengan pendekatan normatif-sosiologi digunakan dalam menganalisis data. Sumber data primer adalah informan, yakni masyarakat yang pindah agama karena perkawinan, pejabat pemerintah, dan agamawan. Selain itu, digunakan bahan pustaka setelah mempelajari secara serius literatur-literatur seperti artikel jurnal, buku, dan dokumen pendukung lainnya, yang relevan dengan penelitian ini. Temuan penelitian menunjukkan bahwa perlindungan hukum terhadap hak-hak perempuan muallaf pasca cerai bukan semata-mata keputusan hakim di atas kertas melainkan tanggung jawab laki-laki yang harus dipenuhi setelah perceraian. Meskipun hak-hak tersebut tidak diwujudkan secara memadai, namun disimpulkan adanya kecenderungan perempuan muallaf untuk mendapatkan hak-haknya dengan kerjasama yang baik dari semua pihak yang berperkara, termasuk para penegak hukum. Studi ini menyarankan bahwa bentuk keberpihakan hukum bagi perempuan berdasarkan hukum tidak hanya di atas kertas sehingga diperlukan evaluasi dari penegak hukum.